(untitled) (Research, Society and Development, 2021)
Objectives: This study aimed to gather and systematize the main available studies, which would clarify the close relationship between the levels of Brain Derived Neurotrophic Factor (BDNF) with depressive disorder. Methodology: 30 articles related to BDNF and depressive disorder from indexing platforms, published between 2017 and 2021, were selected, and the focus was on articles that presented contributions to the theme by associating the two conditions. Results and Discussion: Several studies linking BDNF to depressive disorder demonstrate a relationship between decreased levels of this polypeptide in patients with the pathology when compared to healthy individuals, even serving as a biomarker of the disease, in addition, there was an increase in the levels of this factor when performed specific treatments for depression. Other authors relate the increase in BDNF levels with the performance of physical activities and caloric restriction and suggest the possibility of such activity being considered as an adjuvant treatment to the conventional one. Finally, other studies focus on genetic and epigenetic alterations traceable through genomic analysis that can interfere with BDNF expression and serve as increased risk factors for the development of neuropsychiatric disorders. Conclusion: There is enough evidence to support the statement that BDNF is related and may be a promising tool for the diagnosis and future approaches to the pathology, but further studies are needed to consolidate the findings already demonstrated above, as well as to determine the levels of BDNF to be considered as predictors of disease.